Effectiveness of the National Budget - Kakembo, Sophie Nampewo; Bogere, George (ACODE Policy Dialogue Report Series, 2013)
The Citizens’ Budget Tracking and Information Centre (CBTIC) team at ACODE is grateful to all those actors that took part in making the dialogue a success. We are grateful to 93.3 Kfm and NTV Uganda for partnering with ACODE to have the live debate. We are also grateful to the presenters for having prepared background papers that formed the basis of discussions at the dialogue. Specifically we would like to acknowledge the efforts by Dr Abel Rwendeire (National Planning Authority), Ms Rosetti Nabbumba (Ministry of Finance), and Dr Nichodemus Rudaheranwa (Makerere University Business School). In addition, we are grateful for the contributions made by the panel of experts; Dr Augustus Nuwagaba (Makerere University), Dr Fred Muhumuza (Ministry of Finance), Mr Francis Kamulegeya (Price Waterhouse Coopers) and Mr Charles Ocici (Enterprise Uganda). We are also grateful to the Embassy of the Kingdom of the Netherlands and the International Budget Partnership (IBP) for the financial support.
Taking Stock of Fiscal Expenditure Outcomes in Uganda